Implementation of the Filing System at State Elementary School 18 Lawang Kidul - Ema Ambiapuri; Sudirman Sudirman; Putri Hana Pebriana; Heri Dermawan; Emy Yunita Rahma Pratiwi (Edumaspul: Jurnal Pendidikan, 2023)
The research objective is to determine how the filing system is implemented at SDN 18 Lawang Kidul and the supporting and inhibiting factors for implementation. This study uses a qualitative descriptive method using critical information, namely the head of administration and supporting informants, namely the principal and teachers—data collection techniques through observation, interviews, and documentation. Data analysis techniques were carried out through data reduction, data presentation, data verification and conclusion. The results of this study indicate that the implementation of the filing system at SDN 18 Lawang Kidul is quite good through several aspects, namely: 1) Guidance, which is carried out so that the filing system can run according to applicable procedures and regulations; 2) Providing motivation, which is given by the school principal to administrative staff and teachers to encourage enthusiasm in implementing the filing system; 3) Communication, which exists between the school principal and administrative staff and teachers has a significant influence on the ongoing implementation of the filing system in conveying information; 4) Coordination, namely ensuring cooperation between school principals, administrative staff, and teachers in implementing the filing system. The supporting factors for implementing the filing system are the use of an appropriate archive storage system and effective communication in archiving as for the inhibiting factors, namely the low quality of human resources and the limited facilities and infrastructure in archiving.